Evasion of Ribonuclease Inhibitor as a Determinant of Ribonuclease Cytotoxicity - Rutkoski, Thomas J. (2008)
Onconase(®) (ONC) is an amphibian member of the bovine pancreatic ribonuclease (RNase A) superfamily that exhibits innate antitumoral activity. ONC has been granted both orphan-drug and fast-track status by the U.S. Food and Drug Administration for the treatment of malignant mesothelioma, and is poised to become the first chemotherapeutic agent based on a ribonuclease. Investigations into the mechanism of ribonuclease-based cytotoxicity have elucidated several important determinants for cytotoxicity, including efficient deliverance of ribonucleolytic activity to the cytosol and preservation of conformation stability. Nevertheless, the most-striking similarity between ONC and bovine seminal ribonuclease, another naturally cytotoxic ribonuclease, is their insensitivity to inhibition by the potent cytosolic ribonuclease inhibitor protein (RI). RI typically binds to its ribonuclease ligands with femtomolar affinity—an extraordinary feat considering the lack of sequence identity among the bound ribonucleases. Mammalian ribonucleases such as RNase A or its human homologue, RNase 1, have the potential to be more desirable chemotherapeutic agents than ONC owing to their higher catalytic activity, low potential for immunogenicity, favorable tissue distribution, and high therapeutic index, but are limited by their sensitivity to RI. These non-toxic mammalian ribonucleases can be transformed into potent cytotoxins by engendering them with RI-evasion using protein engineering strategies such as site-directed mutagenesis, multimerization, fusion to a targeting moiety, and chemical modification. In several instances, these engineered ribonucleases exhibit greater cytotoxicity in vitro than does ONC. Herein, we review the biochemical characteristics of RI·ribonuclease complexes and progress towards the development of mammalian ribonuclease-based chemotherapeutics through the elicitation of RI-evasion.